Eutrichophilus cordiceps Mjöberg, 1910 (Ischnocera: Trichodectidae) in Spiny Tree Porcupines (Coendou villosus): New locality records and the first molecular evidence of association with Bartonella sp. - Bassini-Silva, Ricardo [UNESP]; Chagas, Maria Eduarda Moraes das [UNESP]; Mello-Oliveira, Victor de Souza [UNESP]; Calchi, Ana Cláudia [UNESP]; Castro-Santiago, Ana Carolina; Andrade, Lívia de Oliveira [UNESP]; Benedet, Gabriela Coelho; Pereira, Fernanda Mara Aragão Macedo; Soares-Neto, Lauro Leite; Hippólito, Alícia Giolo; Hoppe, Estevam Guilherme Lux [UNESP]; Werther, Karin [UNESP]; et al. (Elsevier, 2024)
The chewing louse genus Eutrichophilus Mjöberg has 19 species only associated with porcupines (Rodentia: Erethizontidae). Of these species, E. cercolabes, E. cordiceps, E. emersoni, E. minor, E. moojeni, and E. paraguayensis have been recorded in Brazil. In the present study, we report E. cordiceps for the first time in the São Paulo State (Bauru Municipality) and for the second time in the Santa Catarina State (Lages Municipality), providing scanning electron images and light microscopy for the eggs, as well as the first molecular data (18S rRNA) for the genus. Additionally, Bartonella sp. was detected for the first time in this chewing lice species.
Keywords: Chewing louse; Ectoparasites; Erethizontidae; Molecular analysis; New World porcupines; Pathogens